IDENTIFIKASI JENIS DAN NILAI SUMMED DOMINANCE RATIO (SDR) GULMA DI LAHAN KERING - lubis, wildan; Umami Harahap, Wahyuni; Nurhajijah (RADIKULA: Jurnal Ilmu Pertanian, 2022)
ABSTRACT Weeds are unwanted plants and can harm plants so that they can reduce production. The study, entitled identification of species and the value of the summed dominance ratio, was conducted in Limau Manih, Padang, North Sumatra for four months. This study aims to identify the type and value of the summed dominance ratio. The tools used are gembor, meter, machete, cart, knife, hoe, dipper, blender and caliper. While the materials used were fresh Sembung Rambat leaves, seeds, drum fertilizer, raffia rope, polybags, plastic, compost, NPK-Mg. The method used in this research is Completely Randomized Design by making five plots where the five plots will be observed and searched for absolute density values, relative density, absolute frequency, relative dominance, significant value index and SDR. This research is an experiment conducted using several types of weeds, namely; Ageratum conyzoides L, Axonopus compresus, Bidens pilosa L, Boreria alata, Borreria leavis, Brachiaria reptans , Calopogonium mucunoides, Chromolaena odorata L, Cleome rutidosperma DC, Crotalaria mucronate, Cynodon dactylon L, Cyperus kyllingenecha, Digitaschyllingera incha , Melastoma affine, Mimosa pudica, Phillanthus amarus, Uraria lagopodioides L. The results showed that the weed with the highest land tenure value in dry land was Brachiaria reptans. Because it has many seeds and strong rhizomes, it belongs to the C4 species. Keyword: weed, summed dominance ratio, weed identification